2020
DOI: 10.1021/acs.joc.0c01180
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Multicomponent Rearrangements via 2-((Quinoxalin-3(4H)-on-2-yl)(aryl)methylene)malononitriles, Generated In Situ, for Divergent Synthesis of Pyrroles with Different Substitution Patterns

Abstract: New three-component domino reactions, providing divergent approaches to multifunctionalized pyrroles with different substitution patterns, have been established (47 examples). In this work, a new rearrangement of quinoxalinones with the participation of the in situ-generated 2-en-1-imine moiety of the substituent at C3 makes it possible to construct two new heterocyclic systems, namely, a benzimidazolone and a pyrrole, simultaneously under one-pot reaction conditions. The reaction is easy to perform simply by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…In 2000, we discovered the acid‐catalyzed rearrangement of 3‐aroylquinoxalin‐2‐ones into 2‐(benzimidazol‐2‐yl)quinoxalines when exposed to 1,2‐benzenediamines [8] . In the last two decades, we have published a series of works on the rearrangement of quinoxalin‐2‐ones via the proposed spiro‐quinoxalinone [9] intermediates ( A ) into 2‐hetarylbenzimidazoles [9a–h] ( B , Type I) as well as 1‐hetarylbenzimidazolones in cases of enamine nucleophiles ( C , Type II, Scheme 1), [9i–k] thus opening a simple way to access various 2‐hetarylbenzimidazoles and 1‐hetarylbenzimidazolones according to the S N (ANRORC) mechanism (i. e., via sequential steps of addition of nucleophile, ring‐opening and ring‐closing) [10] . It was shown that the type of rearrangement may depend on the fact if tautomerizable hydrogen is available or not in the spiro‐forming ring within A .…”
Section: Methodsmentioning
confidence: 99%
“…In 2000, we discovered the acid‐catalyzed rearrangement of 3‐aroylquinoxalin‐2‐ones into 2‐(benzimidazol‐2‐yl)quinoxalines when exposed to 1,2‐benzenediamines [8] . In the last two decades, we have published a series of works on the rearrangement of quinoxalin‐2‐ones via the proposed spiro‐quinoxalinone [9] intermediates ( A ) into 2‐hetarylbenzimidazoles [9a–h] ( B , Type I) as well as 1‐hetarylbenzimidazolones in cases of enamine nucleophiles ( C , Type II, Scheme 1), [9i–k] thus opening a simple way to access various 2‐hetarylbenzimidazoles and 1‐hetarylbenzimidazolones according to the S N (ANRORC) mechanism (i. e., via sequential steps of addition of nucleophile, ring‐opening and ring‐closing) [10] . It was shown that the type of rearrangement may depend on the fact if tautomerizable hydrogen is available or not in the spiro‐forming ring within A .…”
Section: Methodsmentioning
confidence: 99%
“…A. Mamedov and coworkers reported a novel threecomponent domino reaction allowing for multiple approaches to multi-functionalized pyrroles 75 with diverse substitution patterns. [27] The reaction is simple to carry out, requiring only mixing three common reactants and high temperature. Along with quinoxalin-3(4H)-ones 72 and malononitrile 73, secondary amines 74 were used as the third component of the reaction, which is responsible for the type of substituents at 5 th position of the pyrrole ring.…”
Section: Other Annulation Reactions Of C-acyliminesmentioning
confidence: 99%
“…V. A. Mamedov and coworkers reported a novel three‐component domino reaction allowing for multiple approaches to multi‐functionalized pyrroles 75 with diverse substitution patterns [27] . The reaction is simple to carry out, requiring only mixing three common reactants and high temperature.…”
Section: Cycloaddition Reactionsmentioning
confidence: 99%
“…et al (Scheme 61). [60] The reaction mechanism involves Knoevenagel condensation of quinoxalinones 184 with malononitrile followed by in situ generation of 2-en-1imine under nucleophile action. The intermediate B undergoes Intramolecular cyclization and rearrangement allowing to ChemistrySelect construct heterocyclic systems, containing pyrrole and benzimidazolone cores.…”
Section: Synthesis From Nitrilesmentioning
confidence: 99%